2019
DOI: 10.3892/mmr.2019.10902
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin suppresses epithelial‑to‑mesenchymal transition in the MG‑63 cell line

Abstract: epithelial-to-mesenchymal transition (eMT) is a major process involved in tumor progression and metastasis. Melatonin is secreted by the pineal gland and has been documented as a potential therapeutic agent for multiple tumors. However, the effects of melatonin on eMT during osteosarcoma (oa) development remain undefined. The present study explored the biological functions and effects of melatonin on eMT induced by transforming growth factor β1 (TGF-β1) and its underlying mechanisms in MG-63 cells. using weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Similar results were also obtained in osteosarcoma MG-63 cells, where results pointed toward a role of melatonin in suppressing the EMT via HIF-1α/Snail/MMP-9 signaling. These studies revealed that the melatonin treatment caused an increase in the ratio of E-cadherin/N-cadherin in tumor cells while suppressing Snail and MMP-9 levels [ 123 ]. Additionally, in vitro studies using human HCT15 and SW620 colorectal cancer cells showed that the melatonin treatment had a regulatory effect on E-cadherin and Snail-expression levels while exerting weak cytotoxicity [ 124 ].…”
Section: Melatonin As An Inhibitor Of the Epithelial-to-mesenchymal T...mentioning
confidence: 99%
“…Similar results were also obtained in osteosarcoma MG-63 cells, where results pointed toward a role of melatonin in suppressing the EMT via HIF-1α/Snail/MMP-9 signaling. These studies revealed that the melatonin treatment caused an increase in the ratio of E-cadherin/N-cadherin in tumor cells while suppressing Snail and MMP-9 levels [ 123 ]. Additionally, in vitro studies using human HCT15 and SW620 colorectal cancer cells showed that the melatonin treatment had a regulatory effect on E-cadherin and Snail-expression levels while exerting weak cytotoxicity [ 124 ].…”
Section: Melatonin As An Inhibitor Of the Epithelial-to-mesenchymal T...mentioning
confidence: 99%
“…Curcumin suppresses colon cancer growth and metastasis, associated with upregulated epithelial markers and downregulated mesenchymal markers as well as EMT-related transcription factors Snail and Twist [ 102 ]. Chen et al showed that the anticancer effects of melatonin on osteosarcoma OA MG-63 cells were mediated by the inhibition of EMT through the HIF-1α/Snail/MMP 9 signaling pathways [ 103 ]. Prostate cancer stem cells with a mesenchymal phenotype are triggered by cancer-associated fibroblasts (CAFs) by HIF-1α/β-catenin-dependent signaling pathways [ 104 ].…”
Section: Ps Involvement In Tumor Metastasis By Mediating Coagulationmentioning
confidence: 99%
“…In addition, melatonin was found to suppress RSK2 via the HER2/MAPK/Erk pathway to inhibit EMT in breast cancer cells [ 148 ]. Besides these pathways, melatonin has also been shown to inhibit transforming growth factor beta-induced EMT in MG-63 osteosarcoma cells via the HIF-1/Snail/MMP-9 pathway [ 149 ].…”
Section: Potential Therapeutic Mechanisms Of Melatonin In Endometriosismentioning
confidence: 99%